Two new genetically modified mouse alleles labeling distinct phases of retinal ganglion cell development by fluorescent proteins. Issue 12 (28th August 2020) - Ge, Yichen; Wu, Fuguo; Cheng, Mobin; Bard, Jonathan; Mu, Xiuqian
Abstract: Background: During development, all retinal cell types arise from retinal progenitor cells (RPCs) in a step‐wise fashion. Atoh7 and Pou4f2 mark, and function in, two phases of retinal ganglion cell (RGC) genesis; Atoh7 functions in a subpopulation of RPCs to render them competent for the RGC fate, whereas Pou4f2 participates in RGC fate specification and RGC differentiation. Despite extensive research on their roles, the properties of the two phases represented by these two factors have not been well studied, likely due to the retinal cellular heterogeneity. Results: In this report, we describe two novel knock‐in mouse alleles, Atoh7 zsGreenCreERT2 and Pou4f2 FlagtdTomato, which labeled retinal cells in the two phases of RGC development by fluorescent proteins. Also, the Atoh7 zsGreenCreERT2 allele allowed for indirect labeling of RGCs and other cell types upon tamoxifen induction in a dose‐dependent manner. Further, these alleles could be used to purify retinal cells in the different phases by fluorescence assisted cell sorting (FACS). Single cell RNA‐seq analysis of purified cells from Atoh7 zsGreenCreERT2 retinas further validated that this allele labeled both transitional/competent RPCs and their progenies including RGCs. Conclusions: Thus, these two alleles are very useful tools for studying the molecular and genetic mechanisms underlying RGC formation. Key Findings: We report the generation and characterization of two knock‐in mouse alleles, which label retinal cells in two phases of retinal ganglion cell genesis by different fluorescent proteins. One allele also allows for inducible indirect labeling of retinal ganglion cells. These alleles enable the isolation of retinal cells in the two phases by fluorescence assisted cell sorting (FACS). The purified cells can be characterized by genomic means such as single cell RNA‐seq.